Combining Beers and STOPP Criteria to Identify Inappropriate Medication Use in Elderly Patients with Chronic Diseases and Polypharmacy - Abdillah Mursyid; Farahdina Chairani; Yusransyah Yusransyah; Devi Pujiati (Sanata Dharma University, 2025)
Elderly individuals often suffer from multiple chronic conditions thatrequire the prescription of various medications. This can increase therisk of being prescribed Potentially Inappropriate Medications (PIMs).The research objective was to evaluate the effectiveness of Beers 2019and STOPP version 2 2016 criteria in detecting PIMs and theircorrelation with adverse drug events among geriatric patients whowere admitted to the Hospital. The researchers conducted aretrospective analysis of the 100 patients' medical records admitted tothe hospital in 2022. Beers 2019 criteria were more effective inidentifying PIMs than STOPP version 2 2016 criteria. Using Beers 2019criteria, 31 cases of PIMs were identified among the 100 patients whomet the inclusion criteria, while only 25 cases were identified usingSTOPP version 2 2016 criteria. Alprazolam was the most frequentlyprescribed medication (19.54%) in the first criteria of Beers 2019,followed by ranitidine in category two and spironolactone in category5, each named for seven cases (22.58%). The most commonly foundPIMs, according to STOPP version 2 2016 criteria, were domperidone(40.00%) and spironolactone (28.00%). The study recommends thatclinicians and pharmacists work together to develop critical supportivedata to enhance the identification of potentially inappropriatemedications.